To simplify the expression, let's expand the brackets:
9(k + 13) + 10(12k - 1)
= 9k + 9(13) + 10(12k) + 10(-1)
= 9k + 117 + 120k - 10
= (9k + 120k) + (117 - 10)
= 129k + 107.
add 9(k+13)+10(12k−1)
3 answers
Use the properties of operations to add 9(k+13)+10(12k−1).(1 point)
To add the expression 9(k + 13) + 10(12k - 1), we can use the distributive property of multiplication over addition.
First, distribute 9 to both terms inside the first bracket:
9(k + 13) = 9k + 9(13) = 9k + 117.
Next, distribute 10 to both terms inside the second bracket:
10(12k - 1) = 10(12k) - 10(1) = 120k - 10.
Finally, combine the like terms:
9k + 117 + 120k - 10 = (9k + 120k) + (117 - 10) = 129k + 107.
Therefore, 9(k + 13) + 10(12k - 1) simplifies to 129k + 107.
First, distribute 9 to both terms inside the first bracket:
9(k + 13) = 9k + 9(13) = 9k + 117.
Next, distribute 10 to both terms inside the second bracket:
10(12k - 1) = 10(12k) - 10(1) = 120k - 10.
Finally, combine the like terms:
9k + 117 + 120k - 10 = (9k + 120k) + (117 - 10) = 129k + 107.
Therefore, 9(k + 13) + 10(12k - 1) simplifies to 129k + 107.